Hubungan Konsumsi Tablet Fe, Kunjungan Antenatal, dan Keikutsertaan Kelas Hamil dengan Kejadian Stunting pada Balita - sugianti, elya (JURNAL RISET GIZI, 2021)
Background: Stunting causes serious problems for the growth, development, and health status of children under five years. Low access to health services increases the risk of children under five years becoming stunted.Objective: The purpose of this study was to analyze the relationship between consumption of Fe tablets, antenatal visits, and participation in pregnant classes with the incidence of stunting in children aged 24-59 months.Methods: This type of research is an observational study with a case-control design. The number of samples was 292 pairs of mothers and children aged 24-59 months. Data collection by interview and measurement. Data analysis used univariate and bivariate analysis with chi-square testResults: The results showed that 62.3% of stunted children's mothers consumed Fe tablets, 92.5% of stunted children's mothers attended antenatal visits, and 30.8% of stunted children's mothers attended pregnant classes. There was no significant relationship between consumption of Fe tablets (p=0.050), antenatal visits (p=1,000), and participation in pregnant classes (p=0.384) with stunting in children aged 24-59 months.Conclusion: Consumption of Fe tablets, antenatal visits, and participation in pregnant classes were not associated with stunting in children aged 24-59 months.Â Â